(untitled) (Nigerian Journal of Technology, 2018)
Researchers, system operators, engineers, and utility owners are making extensive efforts to fully utilize the installed facilities of power systems in response to increasing energy demand and thereby creating security challenges for power systems. Thus, this paper addresses the problem of power system security using the risk-based security assessment. A linearized risk-based method which uses fast decoupled load flow algorithm was used to assess the low voltage security of power systems. The method is based on the concept of risk, which considers both the likelihood of occurrence and the severity of the contingency. It requires the probability of voltage distribution, the probability of contingency and severity function to evaluate the impact of the contingency. The proposed method was illustrated on a real power system, the simulation model of the Nigerian 41 bus 330kV transmission grid network for calculating the risk indices of three simulated contingencies at various rates of occurrence. The calculated risk indices show that as the rate of occurrence increases, risk indices increase. This indicates that contingencies with high rate of occurrence with little impact possess higher or equivalent risk to contingencies with great impact, which rarely occur. Therefore, system operator, technician, and engineer should quickly identify, investigate, and proffer solution to them in order to alleviate their effects on the network and improve service delivery. http://dx.doi.org/10.4314/njt.v37i3.24